The Antecedents of Employees' Innovative Behavior in Manufacturing Industry - Muna Wadhiha, Mohd Fauzi (2009)
The purpose of this research is to study empirically the relationship between leadership,organization culture, knowledge management, job satisfaction and employees’ innovative behavior. Employees’ innovative behavior is considered a vital link for manufacturing organization to compete in the global competition. The variables in this research used the7 point scales: innovative behavior (14 questions), job satisfaction (6 questions),leadership (6 questions), organization culture (6 questions), and knowledge management(5 questions).The research employed the quantitative methodology to examine the relationship between independent variables, dependent variable and mediating factors. The questionnaires were based on feedback of employees from Asian Composite Manufacturing (ACM) and INTEL. A total of 211 employees were selected randomly as samples of the study.The hypotheses in this research are tested using structural equations modeling (SEM). The research indicates direct effects that leadership has a significant positive direct effect on job satisfaction, while organization culture has a positive and insignificant direct effect on job satisfaction, and knowledge management has a negative and insignificant direct effect on job satisfaction. Besides that, results also indicate that leadership has a negative significant direct effect on employees’ innovative behavior. Organization culture has a negative significant direct effect on employees’ innovative behavior. Knowledge iii management has a positive significant on employees’ innovative behavior and job satisfaction are positive and significant on employees’ innovative behavior.The study also found several significant indirect paths effects or mediating paths. Firstly,leadership has a positive and significant effect on employees’ innovative behavior through the job satisfaction. Secondly, organization culture has a positive and insignificant effect on employees’ innovative behavior through job satisfaction. However,there is one negative and insignificant relationship between knowledge management and employees’ innovative behavior through job satisfaction.